Learning Strategy to Read The Qur'an Online Using The At-Tibyan Method - Efrita Norman; Arman Paramansyah; Rizki Firmansyah (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to describe the implementation of the At-Tibyan method in read the Al-Qur’an online at Graha Qur’an Wadi Mubarak, as well as the strategies and factors that support or inhbiting read the Al-Qur’an online using the At-Tibyan method. The research methodology employed is qualitative research, with 7 participants involved. Data analysis follows the Miles Huberman analysis approach, involving data collection, data reduction, data presentation, and verification/conclusion. The research findings indicate that the At-Tibyan method used in read the Al-Qur’an online at Graha Qur’an Wadi Mubarak involves preparation, implementation, and evaluation stages, and is supported by factors such as qualified instructors and active participant involvement. However, challenges such as poor internet connectivity and limited participant engagement are also encountered.